Association between depression and anxiety and adverse obstetric and neonatal outcomes - Fufei Zhang; Xinran Zhao; Xinlin Huang; Jingyi Huang; Qinfeng Yang; Xuegao Yu; Xiaomin Hou; Mengning Dong (Medicine, 2026)
Maternal depression and anxiety are common perinatal conditions; however, large-scale, nationally representative evidence on their association with a comprehensive range of obstetric and neonatal outcomes remains limited. The study utilized the International Classification of Diseases, 9th and 10th Revisions, Clinical Modification (ICD-9-CM and ICD-10-CM) to identify diagnostic codes for depression, anxiety, and obstetric outcomes. Data from the National Inpatient Sample were analyzed. Categorical variable differences were assessed via the chi-square test. Univariate and multivariate regression analyses were conducted to evaluate the relationship between maternal depression and anxiety and obstetric outcomes, with forest plots displaying odds ratios and 95% confidence intervals. A total of 6815,408 birth hospitalizations were included, with 323,705 women diagnosed with depression or anxiety. Multivariable analysis showed that birth hospitalizations with a documented diagnosis of depression or anxiety had higher odds of several adverse obstetric and neonatal outcomes, including malformation, severe preeclampsia, chorioamnionitis, major puerperal infection, intrauterine death, placenta previa, premature rupture of membranes, postpartum hemorrhage, fetal growth restriction, endometritis, uterine rupture, placental abruption, and preterm birth. These findings suggest that depression and anxiety diagnoses during birth hospitalization are associated with several adverse obstetric and neonatal outcomes. Maternal mental health history should be considered when assessing perinatal risk and planning care. The results also support continued screening, brief intervention, and referral for mental health concerns during prenatal and postpartum care. Future prospective studies with predelivery mental health assessment are needed to better evaluate the temporal sequence and potential causal pathways.